Integrated metabolomic and transcriptomic analyses reveal that starch and sucrose metabolism regulate maize kernel hardness - Zhou, Haiyu; Xie, Xiaodong; Xie, Hexia; Qin, Lanqiu; Xie, Yuxin; Yang, Xiang; Zhou, Bujin; He, Jingdan; Wang, Bingwei; Shi, Chengqiao; Lv, Juzhi; Tan, Xianjie; et al. (Frontiers in Plant Science, 2025)
Maize kernel hardness, largely determined by the structural and compositional characteristics of the endosperm, is a key trait affecting grain quality, milling performance, and storage stability. Although vitreous and starchy endosperms exhibit markedly different physical properties, the underlying metabolic and transcriptional mechanisms—particularly the crosstalk between primary and specialized metabolic pathways—remain insufficiently understood. In this study, we conducted integrated metabolomic and transcriptomic analyses, along with cytological observations, to investigate these mechanisms using two contrasting maize inbred lines (D003, vitreous; D009, starchy) at three kernel developmental stages (18, 25, and 32 days after pollination, DAP). Cytological examination revealed that D003 endosperms comprise smaller, tightly packed cells containing polygonal starch granules, whereas D009 endosperms consist of larger, irregular cells with loosely arranged spherical starch granules. Metabolomic profiling revealed significantly higher levels of carotenoids—including carotenes (α-carotene, β-carotene) and xanthophylls (zeaxanthin, lutein)—in D003 kernels across all stages, implicating carotenoid biosynthesis in contributing to kernel hardness. Transcriptomic analysis identified starch and sucrose metabolism as the most significantly enriched pathway among differentially expressed genes (DEGs), with qRT-PCR validation confirming the downregulation of a key sucrose synthase gene (Zm00001eb313170). We propose a synergistic model in which transcriptional regulation of starch and sucrose metabolism—particularly reduced sucrose synthase activity—promotes the formation of a compact endosperm structure characterized by polygonal starch granules, while enhanced carotenoid accumulation reinforces cellular interfaces, collectively enhancing kernel hardness. These findings offer novel molecular targets for breeding strategies aimed at improving maize kernel quality.